The Relationship Between the Role of Health Cadres and Compliance with Antenatal Care Visits - Arifah, Eka Shofiyatul; Ishak, Fifi; Husna Ali, Rizky Nikmathul; Pakaya, Salahudin (Jurnal Keperawatan Profesional, 2025)
Antenatal Care (ANC) is an essential health service during pregnancy that aims to detect risks early and maintain the health of the mother and fetus. Although the government has set a minimum standard of six ANC visits, the realization at the Sipatana Health Center in 2023 is still low, with K4 coverage of 34.8% and K6 only 30.5%. This indicates the low level of compliance of pregnant women in making ANC visits. Health cadres have an important role in increasing compliance through education and assistance. This study aims to examine the relationship between the role of health cadres and compliance with ANC visits. The approach used is quantitative with a cross-sectional design. The sample consisted of 50 health cadres selected through total sampling. Data were collected through questionnaires that has gone through validity and reliability tests and documentation of medical records, then analyzed using the Chi-Square Test of Independence. The results showed that 46% of cadres played a less role and 26% were very less, and 60% of pregnant women were not compliant with ANC visits. There is a significant relationship between the role of health cadres and the level of compliance of pregnant women (p = 0.033  OR = 4,09). Conclusion: The role of cadres has a significant effect on compliance with ANC visits. Strengthening the capacity of cadres is very necessary to increase service coverage.